Dose assessment intercomparisons within the RENEB network using G0-lymphocyte prematurely condensed chromosomes (PCC assay). (2nd January 2017) - Terzoudi, Georgia I.; Pantelias, Gabriel; Darroudi, Firouz; Barszczewska, Katarzyna; Buraczewska, Iwona; Depuydt, Julie; Georgieva, Dimka; Hadjidekova, Valeria; Hatzi, Vasiliki I.; Karachristou, Ioanna; Karakosta, Maria; Meschini, Roberta; et al.
Abstract: Purpose: Dose assessment intercomparisons within the RENEB network were performed for triage biodosimetry analyzing G0 -lymphocyte PCC for harmonization, standardization and optimization of the PCC assay. Materials and methods: Comparative analysis among different partners for dose assessment included shipment of PCC-slides and captured images to construct dose-response curves for up to 6 Gy γ-rays. Accident simulation exercises were performed to assess the suitability of the PCC assay by detecting speed of analysis and minimum number of cells required for categorization of potentially exposed individuals. Results: Calibration data based on Giemsa-stained fragments in excess of 46 PCC were obtained by different partners using galleries of PCC images for each dose-point. Mean values derived from all scores yielded a linear dose-response with approximately 4 excess-fragments/cell/Gy. To unify scoring criteria, exercises were carried out using coded PCC-slides and/or coded irradiated blood samples. Analysis of samples received 24 h post-exposure was successfully performed using Giemsa staining (1 excess-fragment/cell/Gy) or centromere/telomere FISH-staining for dicentrics. Conclusions: Dose assessments by RENEB partners using appropriate calibration curves were mostly in good agreement. The PCC assay is quick and reliable for whole- or partial-body triage biodosimetry by scoring excess-fragments or dicentrics in G0 -lymphocytes. Particularly, analysis of Giemsa-stained excess PCC-fragments is simple, inexpensive and its automation could increase throughput and scoring objectivity of the PCC assay.